Modes of presentation of malaria patients attending OPD of medical institutions in Anuradhapura District. - Seneviratne, U.W.A (My University, 1994)
This descriptive study was carried out in the OPD of 7 randomly selected medical institutions in Anuradhapura district,to determine different clinical presentations,in order to create awareness among the clinicians with regard to the patterns of presentation.The study population comprised of all patients whose blood smears were found to be positive for malaria parasites.The predominant species of the study group was plasmodium vivax (80.8 per cent) and P.Falciparum percentage including the mixed infections was 19.2 per cent. The fever patients were categorized according to the subjective feeling of fever as mild,moderate and severe.Estimated mean parasite density of the 3 group were 13171.4,10896.4,14437.2 respectively.Six patterns of clinical presentations were seen among the study population.Pattern 3 consisting of fever headache,backache,muscle and joint pain was significantly higher in adluts than pattern 4 (SND =3.8, p0.01) pattern 4 (fever+headache+gastro intestinal symptoms with or without fits) was found to be significantly higher in the age group 5 years.